Learning history with location-based applications: An architecture for points of interest in multiple layers - Laato, Samuli; Rauti, Sampsa; Laato, Antti; Laine, Teemu H.; Sutinen, Erkki; Lehtinen, Erno (Sensors (Switzerland), 2021)
Location-based applications (LBAs) capture the user’s physical location via satellite navigation sensors and integrate it as part of the digital application. Because of this connection, the real-world environment needs to be accounted for in LBA design. In this work, we focused on creating a database of geographically distributed points of interest (PoIs) that is optimal for learning local history. First, we conducted a requirements elicitation study at three outdoor archaeological sites and identified issues in existing solutions. Second, we designed a multi-layered prototype solution. Third, we evaluated the solution with nine experts who had prior experience with LBAs or similar systems. We incorporated their feedback to our design to iteratively improve it. As a whole, our work contributes to the LBA design literature by proposing a solution that is optimized for the learning of local history.
Keywords: Archaeological site; Digital applications; Location-based applications; Physical locations; Points of interest; Real world environments; Requirements elicitation; Satellite navigation; Crowdsourcing; Edge computing; Education; History; Location-based applications; Pervasive games; Point of interest